2015
DOI: 10.3923/jbs.2015.167.176
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Characterization of Aerobic Xylene-Degrading Bacteria from Gasoline Contaminated Soil Sites Around Gas Stations in Northern Jordan

Abstract: A B S T R A C T Xylene is frequently released into the environment from biomass. As a consequence of this, its bioaccumulation can cause adverse health effects in humans. The purpose of this study was to screen for aerobic xylene-degrading bacteria from gasoline contaminated soil sites located around gas stations in the city of Al-Mafraq, Jordan. The effects of some physicochemical factors were examined. The 10 g of soil sample were transferred to Stanier's mineral medium supplemented with 1% m-xylene and incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
3
7
0
Order By: Relevance
“…strain XYL8 and Bacillus cereus strain PYR9 using Bergey's Manual for Determinative Bacteriology by Holt et al [21]. These findings agree with the reports of Irshaid and Jacob [35], Wanjohi et al [36], Isiodu et al [32] and Fagbemi and Sanusi [37] that two -third of most petroleum hydrocarbon degraders are Gram negatives with one -third being Gram positives but contradict the finding of Kafilzadeh and Pour [16], who reported that more of Gram positive bacteria were isolated than Gram negative bacteria. A lot of rod -shaped bacteria have also been implicated in hydrocarbon degradation studies (Chikere et al [12], Irshaid and Jacob [35], Wanjohi et al [36], Isiodu et al [32] and Fagbemi and Sanusi [37]) and similar result was obtained in this study.…”
Section: Discussionsupporting
confidence: 91%
“…strain XYL8 and Bacillus cereus strain PYR9 using Bergey's Manual for Determinative Bacteriology by Holt et al [21]. These findings agree with the reports of Irshaid and Jacob [35], Wanjohi et al [36], Isiodu et al [32] and Fagbemi and Sanusi [37] that two -third of most petroleum hydrocarbon degraders are Gram negatives with one -third being Gram positives but contradict the finding of Kafilzadeh and Pour [16], who reported that more of Gram positive bacteria were isolated than Gram negative bacteria. A lot of rod -shaped bacteria have also been implicated in hydrocarbon degradation studies (Chikere et al [12], Irshaid and Jacob [35], Wanjohi et al [36], Isiodu et al [32] and Fagbemi and Sanusi [37]) and similar result was obtained in this study.…”
Section: Discussionsupporting
confidence: 91%
“…This contradiction might be due to the nature of the ecosystem as marine environment is generally characterized with lower temperatures unlike the terrestrial ecosystem with higher temperatures. The result in Table 4 showed that the drops in pH are probably because the degradation of the hydrocarbons by these bacteria resulted in the discharge of acidic substances and intermediates (organic acids and other metabolic products) which reduces the pH of the medium and is in agreement with the researches carried out by previous studies [16,25,31]. The result in Table 5 revealed that the degradation and utilization of these compounds resulted in increase in optical density (cell mass) of these bacteria and corroborates with the findings of John et al [18] and Akinbankole et al…”
Section: Discussionsupporting
confidence: 89%
“…Similar result was observed by Athar et al [30]. The result contradicts the report of Irshaid and Jacob [16] that the decrease in temperature from 30 -25°C led to decrease in growth rates of xylene degrading bacteria from gasoline contaminated soil sites while whereas the growth rates almost terminated at 45 °C,. This contradiction might be due to the nature of the ecosystem as marine environment is generally characterized with lower temperatures unlike the terrestrial ecosystem with higher temperatures.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations